Ramping ensemble activity in dorsal anterior cingulate neurons during persistent commitment to a decision - Blanchard, Tommy C. (J Neurophysiol, 2015)
We frequently need to commit to a choice to achieve our goals; however, the neural processes that keep us motivated in pursuit of delayed goals remain obscure. We examined ensemble responses of neurons in macaque dorsal anterior cingulate cortex (dACC), an area previously implicated in self-control and persistence, in a task that requires commitment to a choice to obtain a reward. After reward receipt, dACC neurons signaled reward amount with characteristic ensemble firing rate patterns; during the delay in anticipation of the reward, ensemble activity smoothly and gradually came to resemble the postreward pattern. On the subset of risky trials, in which a reward was anticipated with 50% certainty, ramping ensemble activity evolved to the pattern associated with the anticipated reward (and not with the anticipated loss) and then, on loss trials, took on an inverted form anticorrelated with the form associated with a win. These findings enrich our knowledge of reward processing in dACC and may have broader implications for our understanding of persistence and self-control.